Pemberdayaan Santriwati melalui Pelatihan Inovasi Circular Economy: Daur Ulang Sampah di Pesantren Al-Inayah Kecamatan Rimbo Bujang Kabupaten Tebo - Umi Rossy Mardhiyah; M. Yusuf Aminuddin; Umi Ronna Anisah (Journal of Innovation and Contribution to Community Service, 2025)
Waste is something that has no value and is useless if ignored, but if processed, it can become a source of income. This research aims to educate students about the science and technology that emerges from abandoned waste. This research also provides counseling and guidance to students on the waste recycling process. This practice involves processing waste into products that provide economic value, reducing waste accumulation, and transforming waste into something beautiful when processed. The method used in this research is participatory action research (PAR). The implementation of this PAR method is divided into three stages: preparation, implementation, and evaluation. This research aims to increase students' awareness of the environment within the Al Inayah Islamic boarding school environment, namely in Perintis Village, Rimbo Bujang District, Tebo Regency, Jambi Province. This Community Service Program (PKM) activity aims to increase students' awareness of the environment through training on waste recycling at the Al Inayah Islamic boarding school. And this activity provides many benefits not only for internal parties, namely the Islamic boarding school itself, but also provides benefits to the community in general because it is productive, educational and creative. The results of this activity can improve the quality of students in their life skills which in the future will provide benefits and can be developed further